Associations of saliva cortisol and hair cortisol with generalized anxiety, social anxiety, and major depressive disorder: An epidemiological cohort study in adolescents and young adults. (April 2021) - Kische, Hanna; Ollmann, Theresa Magdalena; Voss, Catharina; Hoyer, Jana; Rückert, Frank; Pieper, Lars; Kirschbaum, Clemens; Beesdo-Baum, Katja
Abstract: Objectives: Most of the observed associations of generalized anxiety disorder (GAD), social anxiety disorder (SAD) and major depressive disorder (MDD) with cortisol concentrations came from clinical and adult study samples, with inconsistent findings, partly due to method variance. We examined cross-sectional and longitudinal associations between GAD, SAD and MDD with saliva and hair cortisol as well as hair cortisol change in a population-based sample of adolescents and young adults, considering relevant co-factors. Design: Epidemiological cohort study in Dresden, Germany. Data of 1050 individuals (mean age: 17.2 years) assessed at baseline (11/2015–12/2016) and of 605 individuals assessed at 1-year follow-up (FU1) are used. Methods: Multivariable regression models were implemented to assess cross-sectional and longitudinal associations of DSM-5 defined 12-month diagnoses of GAD, SAD, and MDD, with short-term (saliva cortisol: cortisol awakening response (CAR) and area under the curve (AUC) as total cortisol) and long-term (hair cortisol) cortisol indices. Multivariable models were adjusted for age or "tanner" stage, waist circumference, tobacco and alcohol consumption, physical inactivity, and hair cortisol dependent confounder. Sex-specific analyses were additionally conducted. Results: Cross-sectional analyses revealed positive associations between SAD and baseline saliva cortisol in multivariable models (CAR: β-coefficient: 0.12; 95% CI: 0.01; 0.23) but could not be confirmed after adjusting for "tanner" stage or comorbid depression. Cross-sectional analyses concerning GAD and MDD in the full baseline sample yielded no significant associations. Sex-specific linear models revealed a significant inverse cross-sectional association between MDD (β-coefficient: − 2.21; 95% CI: − 3.64; − 0.79) as well as SAD (β-coefficient: − 2.21; 95% CI: − 4.03; − 0.38) with baseline hair cortisol in males, but not in females. In longitudinal analyses, no significant associations were found in the fully adjusted model, except for a positive association between hair cortisol change between baseline and FU1 and FU1-SAD (OR: 1.07; 95% CI: 1.02; 1.12). Conclusions: Results confirmed sex-specificity and the role of pubertal development in the association between cortisol with SAD and MDD, while no association emerged regarding cortisol and GAD. Future research in adolescents focusing on the role of cortisol in the pathogenesis of anxiety and depressive disorders would benefit from considering factors like sex-specificity and puberty development as well as comorbidity. Highlights: Positive association between social anxiety and cortisol in adolescents. Sex-specific association between depression and cortisol. Puberty might influence the link between depression/social anxiety and cortisol. No significant association between generalized anxiety disorder and cortisol.